MicroRNA-23b and microRNA-27b plus flutamide treatment enhances apoptosis rate and decreases CCNG1 expression in a castration-resistant prostate cancer cell line - Ruan CA Pimenta; Nayara I Viana; Gabriela Q Amaral; Rubens Park; Denis R Morais; José Pontes; Vanessa R Guimaraes; Juliana A Camargo; Kátia RM Leite; William C Nahas; Miguel Srougi; Sabrina T Reis (Tumor Biology)
The acquisition of a castration-resistant prostate cancer phenotype by prostate cancer cells is the alteration that has the worst prognosis for patients. The aim of this study was to evaluate the role of the microRNAs-23b/-27b as well as the possible CCNG1 target gene in tissue samples from patients with localized prostate cancer that progressed to castration-resistant prostate cancer and in a castration-resistant prostate cancer cell line (PC-3). The microRNAs and target gene expression levels of the surgical specimens were analyzed by quantitative real-time polymerase chain reaction. The prostate cancer cell line, PC-3, was transfected with pre-miR-23b, pre-miR-27b, and their respective controls using Lipofectamine RNAiMAX and exposed or not to flutamide. After transfections, expression levels of both the microRNAs and the gene, CCNG1 , were analyzed by quantitative real-time polymerase chain reaction. The apoptosis and cell cycle assays were performed on the mini MUSE cytometer. MicroRNAs-23b/-27b were underexpressed in surgical specimens of prostate cancer; however, their target gene, CCNG1 , was overexpressed in 69% of the cases. After transfection with the microRNAs-23b/-27b and flutamide, we observed a reduction in gene expression compared with cells that were treated only with microRNAs or only with flutamide. In the apoptosis assay, we demonstrated cell sensitization following transfection with microRNAs-23b/-27b and potentiation when co-administered with flutamide. The number of cells in apoptosis was almost three times higher with the simultaneous treatments (miR + flutamide) compared with the control (p < 0.05). In the cell cycle assay, only flutamide treatment showed better results; a higher number of cells were found in the G0-G1 phase, and a lower percentage of cells completed the final phase of the cycle (p < 0.05). We conclude that microRNAs-23b/-27b are downexpressed in prostate cancer, and their target gene, CCNG1 , is overexpressed. We postulated that microRNAs-23b/-27b sensitize the PC-3 cell line and that after the addition of flutamide in the apoptosis assay, we would observe synergism in the treatments between miR and flutamide. In the cell cycle assay, the use of flutamide was sufficient to decrease the number of cells in mitosis. Therefore, we postulate that microRNAs, along with other drugs, may become very useful therapeutic tools in the treatment of castration-resistant prostate cancer.